Paraneoplastic isolated adrenocorticotropic hormone deficiency revealed after immune checkpoint inhibitors therapy: new insights into anti-corticotroph antibody - Urai, Shin; Watanabe, Miki; Bando, Hironori; Motomura, Yuma; Yamamoto, Masaaki; Tachihara, Motoko; Kanzawa, Maki; Fukuoka, Hidenori; Iguchi, Genzo; Ogawa, Wataru (Frontiers in Immunology, 2023)
Introduction: A recently discovered facet of paraneoplastic adrenocorticotropic hormone (ACTH) deficiency exists in two forms: a paraneoplastic spontaneous isolated ACTH deficiency (IAD) and an immune checkpoint inhibitor (ICI)-related hypophysitis. Autoantibodies against corticotrophs, such as circulating anti-proopiomelanocortin (POMC) antibodies are considered disease markers. However, the number of identified cases was limited, implying that the characteristics of these autoantibodies are not fully understood. Methods: We investigate circulating autoimmune autoantibodies in detail through a novel case of IAD that developed as a paraneoplastic autoimmune ACTH deficiency. Results: The patient developed IAD after 25 weeks of ICI therapy for metastasis of large-cell neuroendocrine carcinoma at 69 years of age. Ectopic ACTH expression and infiltration of CD3+, CD4+, CD8+, and CD20+ lymphocytes were observed in the tumor tissues and circulating anti-POMC antibodies were detected specifically in the patient's serum. Moreover, detailed analyses of immunofluorescence staining using patient serum revealed that the recognition site of the autoantibody was ACTH25-39, which had not been identified in previous cases of paraneoplastic autoimmune ACTH deficiency. Conclusion: This case involved a combination of paraneoplastic spontaneously acquired IAD and ICI-related hypophysitis occupying the middle ground. Moreover, our study reveals new aspects of anti-POMC antibodies in patients with paraneoplastic ACTH deficiency. This report expands our understanding of the immunological landscape and provides new insights for the identification of antibodies associated with paraneoplastic autoimmune ACTH deficiency.